Effects of morphometric and biochemical parameters on collagen and pepsin-solubilized collagen yields of Holothuria tubulosa (Gmelin, 1790) and Holothuria (Roweothuria) poli (Delle Chiaje, 1823) - Künili İbrahim Ender (Oceanological and Hydrobiological Studies)
Due to their unique biochemical composition, sea cucumbers are highly prized marine echinoderm species. One of their most important properties is that they contain a high amount of collagen in their body wall. In this study, the relationship between collagen and pepsin-solubilized collagen yields from Holothuria tubulosa and Holothuria poli and morphometric and biochemical parameters were investigated.